Analisis Dampak Limbah Industri Terhadap Sungai Metro, Bandulan Malang: Tinjauan Terhadap Kesehatan Masyarakat Dan Tindakan Perlindungan Lingkungan - Damianus Ngai Rupi; Emanuel Katarino Mbeo; Yohanes Endi (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The focus of research in this paper is the impact of industrial waste on the Metro River, Bandulan, Malang. The Metro River is one of the small rivers in Malang City which is used by the local community to meet their daily needs. This research study uses the method of studying the encyclical Laudato Si' issued by Pope Francis in response to current environmental problems. From the research studies that have been carried out, researchers found several things that have not been answered by several figures regarding river water pollution by industrial waste. First, industrial waste threatens the survival of future generations. Second, pollution of river water by factory waste will cause or cause disease in those who use the river water. Third, the underground water that people use and suck for consumption may be polluted by industrial waste. Another important issue is that it is very difficult to prevent waste from being dumped into rivers, because some of the residents who work in industry are residents who live around the Metro River. Human awareness is needed to protect and care for the earth so that the earth becomes a safe place for all living creatures to live. In the encyclical Laudato Si', Pope Francis invites humans to love and pay attention to the environment. Allah has created this earth well.